2018
DOI: 10.1021/acsami.8b13215
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Lamellar Mo2C for Electrochemical Hydrogen Production: Insights into the Origin of Hydrogen Evolution Reaction Activity in Acidic and Alkaline Electrolytes

Abstract: Developing high surface area Mo2C with certain crystal plane exposed is an efficient strategy but is an urgent challenge to optimize the hydrogen evolution reaction (HER) catalytic performances. In addition, the effects of certain crystal faces on catalytic performance have been limitedly understood. Toward this end, the (1 0 0) plane oriented two-dimensional lamellar Mo2C transformed from carbon fibers is synthesized successfully in a molten salt system. Subsequently, the electrocatalytic properties toward HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…The extracted slope values from the Tafel plots were 83 and 86 mV dec −1 for the acidic and 65 and 100 mV.dec −1 for the alkali for reduced Mo 2 C and W 2 C, respectively. These values indicate that the Volmer-Heyrovsky reaction step is obeyed for the whole HER process (Bockris and Potter, 1952; Yuan et al, 2018). Another important parameter, the exchange current density (j 0 ), was extracted to evaluate HER activity by extrapolating the linear region of the Tafel plot.…”
Section: Resultsmentioning
confidence: 94%
“…The extracted slope values from the Tafel plots were 83 and 86 mV dec −1 for the acidic and 65 and 100 mV.dec −1 for the alkali for reduced Mo 2 C and W 2 C, respectively. These values indicate that the Volmer-Heyrovsky reaction step is obeyed for the whole HER process (Bockris and Potter, 1952; Yuan et al, 2018). Another important parameter, the exchange current density (j 0 ), was extracted to evaluate HER activity by extrapolating the linear region of the Tafel plot.…”
Section: Resultsmentioning
confidence: 94%
“…Most of the research articles and reviews reported that the inferior performance of electrocatalysts in alkaline solution to the acidic one is due to the extra energy required in the Volmer step. 4,20 However, several emerging catalysts (e.g., Ru-MoO 2 , 21 MoO 2 /α-Mo 2 C, 22 Mo 2 C, 23,24 Mo 2 C/G-NCS, 25 C-CWC, 26 DR-MoP, 27 NiCo 2 P 2 -ACNT, 28 NCP, 29 NiCo 2 P x , 30 Ni-Cu-P 31 ) have been developed which are active both in acid and alkaline media and demonstrate better catalytic capability in alkaline electrolytes than in acidic media. Nevertheless, there is a lack of understanding of their better performance in alkaline solutions.…”
Section: Electrochemistry Of Hydrogen Evolution In Alkaline Solution mentioning
confidence: 99%
“…234 The d orbitals of M atoms will be broadened with the help of sand p-orbitals of C atoms, thus forming a similar Pt d-band state. 235 Recently, TMCs like Mo x C y , 23,235,236 W x C y , 237,238 39,239 and Ni x C y 240 have been applied in alkaline HER, especially Mo 2 C. An informative summary can be found in the latest review. 235 Despite these advantages, the relatively poor conductivity of TMCs requires a highly conductive substrate.…”
Section: Transition Metal Carbidesmentioning
confidence: 99%
“…According to the corresponding Tafel slope (Figure 5b), the mechanism of the HER was studied [18] . The three reaction equations in alkaline medium as an example are shown as follow, [19] trueVolmer4ptreaction:4ptnormalH2normalO+normalM+normale-normalM-Hads+OH- trueHeyrovsky4ptreaction:4ptnormalH2normalO+normalM-Hads+normale-normalM+OH-+normalH2 …”
Section: Resultsmentioning
confidence: 99%